KAJIAN EFIKASI HERBISIDA AMETRIN DAN KOMBINASI AMETRIN + (2,4-D ATAU METIL METSULFURON) TERHADAP PERTUMBUHAN GULMA PADA BUDIDAYA TANAMAN TEBU LAHAN KERING - Herry Susanto; Rusdi Evizal; Sugiatno Sugiatno (JURNAL AGROTROPIKA, 2020)
Weed control in dry land cane cultivation is usually done chemically with the pre-emergence herbicides spraying since planting until to one week and post-emergence for about 2.5 months. Pre-emergence herbicides are usually used to control weeds when planting until to 2 month periode and 2.5 months post-emergence herbicides to prepare a second fertilization so that sugar cane growth is not disturbed by weeds. The treatment consisted of: ametrine 80 % herbicide at doses of 0.8, 1.2, 1.6, 2.0; and 2.4 kg / ha, ametrine 1.6 kg/ha+2,4-D 865g l/ha,ametrine 1.6 kg/ha + metil metsulfuron 8 g/ha, 2 times manual weeding treatment, and control. The experimental design used was randomized block design with 4 replications. The results showed that the herbicides ametrine and ametrine + 2,4-D or metsulfuron methyl were able to suppress the total weeds growth in the cultivation of dry land sugarcane. Ametrine and ametrine + 2,4-D or metsulfuron methyl all doses are able to suppress weeds Borreria alata, Rhicardia brasiliensis, and Digitaria longifolia; except at doses of ametrine 0.8 and 1.2 kg/ha against Borreria alata at 8 and 12 weeks after application. Whereas weeds that are not controlled with all treatments, namely Brachiaria sp., Cyperus rotundus, and Cleome rutidosperma. The growth of plant cane is not suppressed by the treatment of herbicide ametrine and ametrine + 2,4-D or metsulfuron  methyl and as well as manual weeding. The treatment of herbicide ametrine and ametrine + 2,4-D or metsulfuron methyl does not cause toxic in plant cane cultivation. Keywords: Ametrine, 2,4-D, metsulfuron methy, plant cane, weeds.